Controlled growth of highly stable and conducting Ge core/ BCN shell nanowire - Choi, Jun Hui; Moon, Ji Yun; Lee, Jae Hyun (Ceramics International, 2024)
Germanium-based nanomaterials have gained prominence as potential enhancers of energy harvesting efficiency and storage capacity, attributed to their superior electrical conductivity, mobility, and lithium-ion storage aptitude. However, their practical application is often hindered by chemical and physical instabilities. In this study, we introduce a facile synthesis method for boron-carbon-nitride (BCN) shell-coated germanium nanowires (Ge@BCN NWs), designed to shield the Ge core from environmental factors while augmenting its electrical conductivity. Through microscopic and spectroscopic analyses, we confirmed the Ge core is completely encapsulated by a highly crystalline BCN shell. Electron transport measurements on the Ge@BCN NWs field-effect transistor (FET) revealed minimal hysteresis alongside heightened electrical conductivity, suggesting that the BCN shell acts as an efficacious protective barrier, curtailing the degradation of Ge NWs. Our approach presents a reliable method for bolstering the stability of nanomaterials and achieving functional 2D coated NWs.
Keywords: Boron carbon nitride; Controlled growth; Core-shell nanowires; Electrical conductivity; Energy storage applications; Ge nanowire; Germaniums (Ge); High stability; Highly stables; Storage capacity; BCN; Core@shell nanowires; Energy storage applications; Ge nanowire; High stability